Identifying and Intervening in Child Maltreatment and Implementing Related National Guidelines by Public Health Nurses in Finland and Japan - Kayoko Suzuki; Eija Paavilainen; Mika Helminen; Aune Flinck; Natsuko Hiroyama; Taiko Hirose; Noriko Okubo; Motoko Okamitsu (Hindawi Limited, 2017)
Aim. This study aimed to investigate how public health nurses identify, intervene in, and implement the guidelines on child maltreatment in Finland and Japan and to compare the data between the two countries. Method. This study employed a cross-sectional design. Public health nurses' knowledge and skills with respect to child maltreatment prevention were assessed using a questionnaire consisting of three categories: identification, intervention, and implementation of guidelines. Public health nurses working in the area of maternal and child health care in Finland (n=193) and Japan (n=440) were the participants. Results. A significantly higher percentage of Japanese public health nurses identified child maltreatment compared to Finnish public health nurses, while Finnish nurses intervened in child maltreatment better than their Japanese counterparts. In both countries, public health nurses who had read and used the guidelines dealt with child maltreatment better than those who did not. Conclusion. The results suggest that effective training on child maltreatment and the use of guidelines are important to increase public health nurses' knowledge and skills for identifying and intervening in child maltreatment.